ESG Practices, Tax Transparency, and Corporate Cash Tax Outcomes - Noviana Nur Ariyani; Umatun Markhumah (Inovasi Analisis Data, 2025)
Purpose – We focus on how corporate tax outcomes are influenced by environmental, social and governance (ESG) practices, in particular we highlight the impact of tax transparency and tax governance disclosure as an important transmission mechanism. It responds to continued discussions about whether corporate tax should be included as part of responsible business in the ESG space. Design/methodology/approach – We follow a hybrid research design that integrates perceptual measures of ESG and tax transparency with objective measures of tax outcomes. Partial least square-structural equation modeling is used to examine the direct, indirect and moderation effects in a model adopted in this study. Findings – The findings show that the quality of governance, strategic ESG integration, and stakeholder pressure are positively related to corporate tax performance directly, and through improved tax transparency. Social practices affect tax liabilities but are realised through mechanisms of transparency, environmental practices have a direct influence. Tax transparency is found to be a key determinant of corporate tax behavior and the perception of enforcement strength does not significantly change this relationship. Originality/value – This paper advances the literature by treating tax transparency as a separate governance measure not subsumed within ESG, thus providing greater theoretical insight into how responsible practices manifest in taxing behaviour. Research Implications – The results have implications for the role of corporate governance and transparency in integrating sustainability strategies with the firm’s tax responsibility.